A review of entrepreneurship in Europe : entrepreneurial ambitions, institutional change, quality entrepreneurship and the potential of social protection - Roshan-Talbot, Sepideh (2021)
Entrepreneurship has the potential to drive economic development and social advancement. The European Commission implemented entrepreneurship policy as a pragmatic response to its economic and social challenges, especially after the 2008 financial crisis. Institutional changes to promote entrepreneurship and enable individuals to directly contribute to economic growth, job creation and society were introduced to create an entrepreneurial Europe. This study undertakes a systematic review to examine the implications of entrepreneurship policy within Europe. Examining and understanding the impacts of entrepreneurship policy and institutional changes are particularly relevant because of the billions of Euros invested and the impacts on the working lives of European citizens. By examining a broad range of existing literature, the study finds that the entrepreneurial Europe envisioned by policymakers has not been fully realised. Instead, entrepreneurship activity has skewed towards poor quality, necessity entrepreneurship. The European institutional context has also shifted away from the social model on which it was founded, increasing the exposure of European workers to social risks. To promote sustainable growth, wellbeing and well-functioning labour markets, researchers and policymakers are reconsidering the role of social protection. Social protection also has the potential to promote quality entrepreneurship. Based on the review of literature, seven testable propositions about how social protection can promote quality entrepreneurship have been developed for future empirical testing. This study advances knowledge in entrepreneurship research and contributes to debates in policymaking and practice. It also provides a sound basis for subsequent empirical research.